A multivariate approach to study the maintenance of soil fertility and soil health in relation to yield and nutrition of rice (Oryza sativa) - Mandal, Mitali; Panda, Narayan; Patra, Prasanta Kumar (ORYZA-An International Journal of Rice, 2021)
Understanding the relationship between soil properties and grain yield and yield related traits is an important objective in crop production programme. The purpose of this study was to evaluate maintenance of soil health in terms of soil chemical properties in relation to rice yield using multivariate analytical methods. Canonical correlation analysis is one of the most popular multivariate analysis techniques to estimate dependent relationship between soil properties with grain yield and yield attributing characters .In this study, five canonical correlation coefficients ( CCCs) were estimated and the first three of them were significant( R1: 1, R2: 0.99 and R3: 0.84, p